2019
DOI: 10.1177/0363546519840278
|View full text |Cite
|
Sign up to set email alerts
|

The Medial Patellofemoral Ligament Is a Dynamic and Anisometric Structure: An In Vivo Study on Length Changes and Isometry

Abstract: Background: Medial patellofemoral ligament (MPFL) reconstruction is associated with a high rate of complications, including recurrent instability and persistent knee pain. Technical errors are among the primary causes of these complications. Understanding the effect of adjusting patellofemoral attachments on length change patterns may help surgeons to optimize graft placement during MPFL reconstruction and to reduce graft failure rates. Purpose: To determine the in vivo length changes of the MPFL during dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 81 publications
(88 reference statements)
4
65
0
2
Order By: Relevance
“…17 The in vitro studies that measured the path length between femoral and patellar attachment points for a graft showed a wide variety of results, including a decrease in graft length with flexion, 27 isometric function over the flexion range, [23][24][25][26] and an increase in graft length with flexion. 28 Previous studies that measured the path length with computational models reconstructed from imaging data of subjects indicated that graft length decreases with flexion, 29 decreases in early flexion followed by an increase, 30 and increases in early flexion followed by a decrease 31 Differences with respect to the previously published data are likely related to the experimental approach. The previous studies did not directly measure tension within the graft or consider the intraoperative graft tensioning protocol included in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…17 The in vitro studies that measured the path length between femoral and patellar attachment points for a graft showed a wide variety of results, including a decrease in graft length with flexion, 27 isometric function over the flexion range, [23][24][25][26] and an increase in graft length with flexion. 28 Previous studies that measured the path length with computational models reconstructed from imaging data of subjects indicated that graft length decreases with flexion, 29 decreases in early flexion followed by an increase, 30 and increases in early flexion followed by a decrease 31 Differences with respect to the previously published data are likely related to the experimental approach. The previous studies did not directly measure tension within the graft or consider the intraoperative graft tensioning protocol included in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…181 This approach also revealed that reconstructing the medial patellofemoral ligament (MPFL) to a location posterior and proximal to its anatomic femoral attachment results in the most isometric graft behaviour during lunging. 90 Similarly, at the shoulder, virtual fibre elongation techniques have allowed an insight into otherwise difficult to access dynamic musculoskeletal interactions. Maximal external rotation at 90°abduction significantly elongates the anterior bundle of the inferior glenohumeral ligaments while only slightly elongating the posterior bundle.…”
Section: Key Findingsmentioning
confidence: 99%
“…Significant uncertainty in reported ligament lengths originates from both the identification of the tissue attachment footprints and virtual fibre insertion sites within the footprint. 90 The determination of ligament insertion sites on MR images can show large variations especially in some ligaments like the sMCL, which has large attachment areas (nearly 400 mm 2 on its tibial proximal attachment). 98 However, for other ligaments such as the ACL, footprints can be accurately identified from MRI images.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual uoroscopic imaging system (DFIS)-based tracking technique has been extensively applied to capture the motion of in vivo lower limb joints during gait and allowed accurate quanti cation of 3D joint kinematics [9][10][11]. Recently, some researchers have used the DFIS for the measurement of soft tissue length changes during motion [12,13]. However, it has not been used to quantify the effects of THA on the hip muscle lengths and moment arms.…”
Section: Introductionmentioning
confidence: 99%